2022
DOI: 10.1186/s12888-022-04343-x
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant interhemispheric functional connectivity in major depressive disorder with and without anhedonia

Abstract: Objective Anhedonia is a core feature of major depressive disorder (MDD), and as a subtype of depression, MDD with anhedonia may have exceptional neurobiological mechanisms. However, the neuropathology of anhedonia in MDD remains unclear. Thus, this study aimed to investigate the brain functional differences between MDD with and without anhedonia. Methods A total of 62 individuals including 22 MDD patients with anhedonia, 20 MDD patients without an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…In addition, MFG is one part of dlPFC, get closely correlated with eudemonia well-being (113). And the increased Voxel-mirrored homotopic connectivity values in the SFG in MDD patients with anhedonia were found from a recent study (114). We speculate that decreased rsFC of right Nac core-like subdivision with right MFG and right SFG in MDD patients indicates that the reward system in MDD with consummatory anhedonia is disrupted.…”
Section: Discussionmentioning
confidence: 54%
“…In addition, MFG is one part of dlPFC, get closely correlated with eudemonia well-being (113). And the increased Voxel-mirrored homotopic connectivity values in the SFG in MDD patients with anhedonia were found from a recent study (114). We speculate that decreased rsFC of right Nac core-like subdivision with right MFG and right SFG in MDD patients indicates that the reward system in MDD with consummatory anhedonia is disrupted.…”
Section: Discussionmentioning
confidence: 54%
“…Cerebral functional nodal characteristics of the left SFG were associated with the severity of consummatory anhedonia in MDD patients with severe anhedonia [ 103 ]. And abnormal voxel-mirrored homotopic connectivity values in the SFG in MDD patients with anhedonia were found in a recent study [ 104 ]. During the reward outcome stage, the right MFG showed decreased activation in MDD patients compared to controls [ 105 ].…”
Section: Discussionmentioning
confidence: 94%
“…This explains the abnormalities of emotional control [45] and hearing impairment [46] seen in patients with MDD. In addition, analysis of dynamic brain graphs generated by BDANet showed that TE1m had the most significant ab- normalities in functional connectivity with other brain regions, possibly related to anhedonia in MDD [47], which are a core symptom of MDD [48]. The degree of abnormal functional connectivity of p24, showed a significant correlation with the severity of clinical symptoms of MDD.…”
Section: Discussionmentioning
confidence: 95%